Benefits and Costs of Poland’s Cooperation with the International Monetary Fund in the Years 2009–2013 - Nowacka-Bandosz, Katarzyna Ewa (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The article discusses the main areas of Poland’s cooperation with the International Monetary Fund implemented during conditions of increasing tension in international markets due to the outbreak of the global financial and economic crisis. The first part presents major lending policy improvements and enhanced IMF resources in response to the global economic crisis. The second part discusses the implications of Poland’s access to the Flexible Credit Line, and the third shows the effects of participation in enhancing the financial resources of the IMF. They were associated with measurable costs for Poland, but the benefits observed from the point of view of stability and financial security for our economy were more important.